Informational Object Nouns and the mass/count distinction - Sutton, Peter R.; Filip, Hana (Proceedings of Sinn und Bedeutung, 2020)
Most theories of the count/mass distinction analyse concrete nouns (denoting physical entities or stuff), and so, implicitly or explicitly, set abstract nouns to one side. We build on a growing number of recent works that address this gap with our analysis of a class of abstract nouns, Informational Object Nouns (IONs), such as information, evidence, belief, and statement. We argue that by incorporating recent work done by Schmitt (2013, 2017) on the development of a domain general mereological sum operation, we can modify theories of the mass/count distinction for concrete nouns and extend their coverage to the set of IONs. As we also argue, an important factor in extending such theories is that they are grounded in the notion that count nouns are interpreted under individuation schemas, relative to a context (Sutton and Filip 2016b; Filip and Sutton 2017, amongst others).